MANAJEMEN PEMBIAYAAN DI BAITUL MAAL WA TAMWIL BIMA MAGELANG - Affida, Maulina; Rifai, Fuad Yanuar Akhmad; Purwanto (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2024)
This research aims to provide an in-depth understanding of how BMT BIMA channels financing as a Sharia financial entity in Magelang Regency. This research includes qualitative research. Research data was collected using observation, interviews, and analysis of relevant documents for data collection. Data analysis was carried out using an interactive model, including data collection, reduction, verification, and conclusions. The research results show that BIMA has a series of procedures that must be complied with in distributing BMT financing. These procedures include 1) conducting a financing analysis, namely activities carried out to collect data and information needed to analyze the condition of prospective members. 2) Financing approval policy, namely many activities carried out before prospective members obtain financing facilities from BMT BIMA. 3) Financing documents and administration, namely policies relating to procedures and documents that must be prepared. 4) Supervision of financing, namely efforts to prevent early financial losses used for financing. 5) Settlement of financing management problems, namely those related to the mechanisms used by BMT BIMA in resolving financing problems